Study on the Mechanism of Bu-Shen-He-Mai Granules in Improving Renal Damage of Ageing Spontaneously Hypertensive Rats by Regulating Th17 Cell/Tregs Balance. (23rd April 2022) - Zhang, Peng; Song, Xu-Yu; Li, Wen; Wei, Jian-Liang; Cui, Yan-Jun; Qi, Ying-Zi; Chen, Xiu-Bao; Jiang, Yue-Hua; Yang, Chuan-Hua
Abstract : Aim of the Study . The present study was designed to interpret the immunoregulatory effect of Bushen Hemai (BSHM) granules to improve renal damage in ageing spontaneously hypertensive rats (SHRs). We focused on regulation of the Th17 cell/Treg balance and explored the targets of BSHM granules. Methods . Blood pressure and urine biochemical indices were recorded. Renal blood flow was evaluated by renal ultrasonography. Transmission electron microscopy (TEM) and HE staining were used to assess kidney and spleen morphology. Renal fibrosis was assessed using Masson staining. Serum levels of IL-6, IL-10, and IL-17A were measured using ELISAs. The density of ROR γ and Foxp3 in the spleen was observed by immunofluorescence staining. The levels of Th17 cells and Tregs in blood were detected via flow cytometry. Transcriptome sequencing was performed to screen the targets of BSHM granules in hypertensive kidneys. Results . BSHM granules decreased SBP by 21.2 mm·Hg and DBP by 8.8 mm·Hg in ageing SHRs (P < 0.05 ), decreased the levels of urine mALB, β 2-Mg, and NAG (P < 0.01 ), and improved renal blood flow and arteriosclerosis. BSHM granules increased IL-10 expression (P < 0.05 ) while decreasing IL-6 (P < 0.01 ) and IL-17A (P < 0.05 ) levels. BSHM granules improved Foxp3 density and the number of Tregs (P < 0.01 ) and reduced ROR γ t density and the number of Th17 cells (P < 0.01 ). Transcriptome sequencing identified 747 differentially expressed (DE) mRNAs in kidneys after BSHM treatment. GO analysis suggested that BSHM granules act through immunoregulation. Conclusions . BSHM granules attenuated hypertensive renal damage in ageing SHRs, by significantly increasing Tregs and decreasing Th17 cells.